The phenomenon of Irhab (terrorism); meaning, history and causes - Ushama, Thameem (International Institute of Islamic Civilisation and Malay World (ISTAC), International Islamic University Malaysia (IIUM), 2018)
This paper presents a brief study of the history of terrorism, including political, intellectual, cultural, social, economic, individual, and spiritual causes. In addition to analytical historicity, the writer applies qualitative content analysis of Qur’ānic verses and prophetic traditions that are relevant to the Islamic intellectual discourse on the subject. The author clarifies the Arabic term, irhāb, both literally and technically, as per lexicons and contemporary use in political and diplomatic circles. Moreover, a brief analytical survey of definitions taken from select research is offered, included perspectives of Western and Muslim writers. To demonstrate several applications of the term, which are used to identify individuals and groups as "terrorists", the survey also includes meanings and implications from the UN General Assembly, the UN Security Council, the European Union and NATO.